2003
DOI: 10.1046/j.1471-4159.2003.01573.x
|View full text |Cite
|
Sign up to set email alerts
|

Far‐upstream elements are dispensable for tissue‐specific proenkephalin expression using a Cre‐mediated knock‐in strategy

Abstract: Several cis-regulatory DNA elements are present in the 5¢ upstream regulatory region of the enkephalin gene (ENK) promoter. To determine their role in conferring organ-specificity of ENK expression in mice and to circumvent the position effects from random gene insertion that are known to often frustrate such analysis in transgenic mice, we used a Cremediated gene knock-in strategy to target reporter constructs to a 'safe haven' loxP-tagged locus in the hypoxanthine phosphoribosyltransferase (HPRT) gene. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Since Improbizer identified only six motifs, we first considered the top six motifs produced by each of these systems. Among the top six motifs, DMB- reported three motifs (TATA, AP-2, AP-1) that may bind TFs known to control the penk promoter [26,27]. MEME reported one motif (TATA) and Improbiser two (NF-Y, TATA) motifs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Improbizer identified only six motifs, we first considered the top six motifs produced by each of these systems. Among the top six motifs, DMB- reported three motifs (TATA, AP-2, AP-1) that may bind TFs known to control the penk promoter [26,27]. MEME reported one motif (TATA) and Improbiser two (NF-Y, TATA) motifs.…”
Section: Resultsmentioning
confidence: 99%
“…Since DMB and MEME can identify arbitrary number of motifs, we also compared the top 20 motifs generated by DMB and MEME. Seven DMB-derived motifs coincided with known TFBSs (TATA, NF-kappaB, AP-2, AP-1 NFI/CTF, NF-Y, MZF1, MIG1, MBP-1) [26,27] known to control penk promoter. MEME yielded only three known penk promoter motifs (TATA, NFI/CTF, AP-1).…”
Section: Resultsmentioning
confidence: 99%
“…Transgene insertion can be targeted with Cre recombinase after knockin of loxP elements. This so-called 'recombination-medi-ated cassette exchange' allows the creation of new transgenic mice carrying single integrants at predefined loci [38] to aid both comparative analyses [39] and also induction strategies [40].…”
Section: Conditional Knockout By Site-specific Recombination (Cre-loxp)mentioning
confidence: 99%
“…Previous work using a rat model indicated that 2.7 kb 5¢ upstream region of the ENK gene is both necessary and sufficient to govern correct cell-specific expression of the gene [6]. Our recent studies using the cre-lox ''knock-in'' strategy also indicated that the proximal 1.4 kb of the mouse ENK gene is sufficient for organ-specificity but farther upstream DNA elements are required for development-and cell-specific expression of the ENK gene [7]. This 2.7 kb region of the rat, mouse and human ENK genes contains an AT-rich DNA sequence [8][9][10] and interfering with the binding of proteins to this AT-rich DNA element resulted in an altered reporter gene expression [1,11,12].…”
Section: Introductionmentioning
confidence: 98%